Qualitative and quantitative screening of coprophilous fungi for cellulase production - Adeoyo, Olusegun Richard; Inufin, Paul Oluwaseun (CV. Literasi Indonesia, 2026)
Filamentous fungi, especially the herbivore dung-inhabiting (coprophilous), are widely explored for cellulase production owing to their ability to secrete abundant extracellular enzymes, rapid growth, and adaptability to diverse substrates. Microbial enzymes are favoured over plant and animal-derived enzymes due to their ease of production, cost-effectiveness, and genetic manipulation potential. This study isolated, identified, and determined cellulase activity of fungal species from cow dung. Three composite cow dung samples were collected from Ikare-Akoko, Oka-Akoko, and Supare-Akoko. The macroscopic and microscopic features of fungal isolates were used to identify them. Screening for cellulase-producing fungi was assessed using the carboxymethyl cellulose (CMC) agar plate screening method. Cellulase is produced by submerged fermentation, quantified by dinitrosalicylic acid (DNSA) enzyme assay methods, and all experiments were performed in triplicate. The results revealed that the sample from Supare (SUP) had the highest fungal counts of 2.9 × 105 CFU/g, followed by Oka-Akoko (2.7 × 105 CFU/g), and the lowest fungal count of 1.8 × 105 CFU/g was obtained from Ikare-Akoko. A total of nineteen (19) fungal species belonging to 12 genera (Acremonium, Alternaria, Aspergillus, Byssochlamys, Candida, Curvularia, Eurotium, Fusarium, Geomyces, Penicillium, Rhizopus, and Trichoderma) were identified. Thirteen (13) fungal species demonstrated cellulolytic activity with varying efficiencies. Alternaria tenuissima had the highest cellulase activity of 5.79 U/mL, followed by Aspergillus fumigatus (5.31 U/mL) and Penicillium sp (5.14 U/mL). Moderate activity was observed in Trichoderma harzianum, Curvularia geniculata, and Byssochlamys nivea, while Aspergillus glaucus showed the least activity (0.88 U/mL). This study revealed that cow dung harbours diverse cellulolytic fungi with cellulase-producing capacity. Therefore, these fungi are promising candidates for sustainable cellulase production in biofuel generation, waste management, and related biotechnological applications.